Strengthening Business Mindset in Facing Digitalization for the People of Gapan, Philippines - Justita Dura; Fadilla Cahyaningtyas; Rina Dewi Indahsari; Nur Lailatu Aqromi; Siti Nurul Afiyah; Setyorini Setyorini; Samsul Arifin; Karolus Danar Kurniawan; Hironimus Hari Kurniawan; Adriani Kala'lembang (International Journal Of Community Service, 2024)
This community service program aims to increase understanding and digitalization skills among business people in Gapan. This program includes various main activities such as seminars, practical skills training, as well as assistance and mentoring sessions. Participants gain insight into the importance of digitalization, skills in using business software, data management, digital marketing, and e-commerce. Mentoring and mentoring help participants apply knowledge in their business context, overcome practical challenges, and develop an adaptive and innovative mindset. The program results show an increase in participants' awareness, knowledge and skills regarding digitalization. Evaluation through participant satisfaction surveys and training observations indicated a high level of satisfaction and a need for more practical sessions and more intensive mentoring. Overall, this program has succeeded in preparing the people of Gapan to face the digital era and increasing their business competitiveness. Important findings include increased access to technology, knowledge about e-commerce, use of data for business decisions, as well as changes in attitudes and mindsets that are more adaptive and innovative. This program makes a positive contribution to increasing competitiveness and local economic growth